Design of beams using EC 2 - Koh, Yong Sheng (2015)
This report focuses on the comparison of the three different design codes, Eurocode 2(EC2), BS8110 and ACI 318 in terms of the shear calculations for the reinforced concrete beams. Eurocode is currently being used in Singapore as the design code. Before the implementation of the Eurocode, the British code, BS8110 has been in use for a very long time. An additional American code, ACI-318 has been taken for comparison to show how the current Eurocode 2 compares with other international codes in terms of shear design. Hence this report aims to compare the calculated shear resistance from EC2, BS8110 and ACI-318 against the experimental data collated from past research. The comparison is done using the relative shear strength value whereby the ratio of the shear values from the experimental values to the shear resistance value calculated from the codes individually is being calculated (Vexp /Vcal). A higher relative shear strength value indicates a more conservative code and vice versa. In the comparison, the beams were separated into two types, one without shear reinforcement and the other consisting of shear reinforcement. For beams without shear reinforcement, the ACI codes were found to be the most conservative as compared to both the EC2 and BS8110. However, there were some controversies in the data collected for the shear reinforced beams which will be further elaborated in the report. The different factors that affects the shear strength of the concrete were also analyzed to determine the trend whereby the shear strength changes in accordance to these factors. These factors include longitudinal ratio, concrete compressive strength, effective depth of concrete beam and the shear span to effective depth ratio. Each increment in the values of the factors lead to different effects on the conservativeness of the 3 different codes and these differences are showcased in the report.